Implementation Of The Jatmika Learning Model Based On Artificial Intelligence To Improve Students' Critical, Creative, And Reflective Thinking In Creative Literary Writing Learning - Indarti , Titik; Sudikan, Setyo Yuwana; Bahruddin, Muhammad; Afdholy, Nadya (Proceeding of International Joint Conference on UNESA, 2025)
This study aims to describe the implementation of the Jatmika learning model based on artificial intelligence to improve critical, creative, and reflective thinking skills for PBSI undergraduate students of the 2023 cohort, Faculty of Language and Arts, Surabaya State University, in producing creative writing in the form of poetry. This research is qualitative in nature with a descriptive qualitative approach. The research subjects are S-1 Indonesian Language and Literature Education students, Faculty of Language and Arts, Unesa, class of 2023, taking the poetry appreciation course. Data collection techniques through observation, interviews, observation, and documentation. The data was analyzed using reduction, presentation, and verification. The results of this study indicate that creative writing, especially poetry, requires the involvement of lecturers and students in the critical, creative, and reflective use of artificial intelligence (AI). This shows the need for additional skills development. Continuous training and education are key to ensuring that all parties can reap the maximum benefits of this technology.